Implementasi Komunikasi Efektif Dalam Pemberian Pelayanan Prima Di Dinas Perpustakaan Arsip Dan Dokumentasi Provinsi Sulawesi Utara - Gonie, Leidy Elen; Lesnussa, Rejune Junita (Universitas Gajah Putih, 2024)
The purpose of this study was to determine the implementation of effective communication in providing excellent service at the North Sulawesi Provincial Archives and Documentation Library Agency by considering the factors of skills, knowledge and attitudes in the process of providing up to providing messages or information to users both verbally and non-verbally. This research design is qualitative. The focus of the research is the implementation of effective communication in providing excellent service. Selection of informants using proposive sampling technique. Data collection was done by observation, interview, and literature study. Credibility (trust). Communicators must have credibility in delivering messages so that the information conveyed is right on target. Cotext, language and information conveyed must be in accordance with the conditions and environment where communication takes place. Content, the content of the message or material delivered to the audience. Clarity, the information conveyed must be clear so that there is no misunderstanding with the communicant. Continuity and consistency, continuous delivery of information. Capability of Audience, communicant understanding of the content of the message is influenced by factors of educational background, social status and age. Channels of Distributions, the use and selection of media as a means of communication, both print and electronic media so that the information